Self-Efficacy sebagai Mediator Work Environment dalam Memengaruhi Job Satisfaction pada Pink-collar Workers di Surabaya - Asnawi, Anita; Arfani, Mochammad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Pink-collar workers frequently engage directly with customers possessing diverse personalities and demands, requiring strong psychological resilience and interpersonal skills. This study aims to examine the effect of work environment on job satisfaction through the mediating role of self-efficacy among pink-collar workers in Surabaya. A quantitative approach was employed using a survey method involving 100 respondents, selected based on their direct involvement in customer service within the hospitality, education, banking, and retail sectors. Data analysis was conducted using SmartPLS 3.0. The results reveal that the work environment has a positive and significant effect on self-efficacy, indicating that a safe, comfortable, and supportive workplace enhances employees’ confidence in their abilities. Furthermore, self-efficacy significantly influences job satisfaction and partially mediates the relationship between work environment and job satisfaction. The direct effect of work environment on job satisfaction is also significant, affirming that job satisfaction is more likely to occur when the work environment supports employees physically, socially, and psychologically. The research model explains more than seventy-five percent of the variance in job satisfaction, highlighting the importance of integrating both external and internal factors in shaping positive work experiences. These findings provide practical implications for organizations to foster conducive work environments that enhance self-efficacy and job satisfaction among pink-collar employees.